Real Implementation of Information Literacy in the Community for Library Service Transformation Program Based on Social Inclusion - Hidayah, Ahmad (Library of Sultan Agung Islamic University, 2025)
ABSTRACT Libraries are desired as institutions that manage collections of written works, printed works, and/or peer works professionally with a standardized system to meet the educational, research, preservation, information and recreational needs of the users. Therefore, librarians who work in libraries must be professional in managing a library. As stated in Law No. 43 of 2007 concerning Libraries, namely